THE EFFECTIVENESS OF ONLINE LEARNING ON STUDENTS IN UNIVERSITI TEKNOLOGI MARA KELANTAN - Siti Nur Zahirah Omar; Nor Afrina Auni Amran; Wan Aqilah Wan Ahmad; Noor Fatin Syuhada Mat Diah; Nur Azira Izzatie Kamal Marzuki; Ahmad Amirul Hafiz Aili @ Ghazali (Journal of Islamic, Social, Economics and Development, 2024)
The researchers doing this research to study if the factors influencing the effectiveness of online learning on students at UiTM Kelantan have any relationship between the independent variable and dependent variable. A total of 364 respondents have responded to this research, using a thorough research methodology and statistical analysis. The primary factors examined were technology, lecturer influence, surrounding environment, and self-efficacy. The strong positive correlation (r = 0.636, p < .01) between technology and online learning. The research found a strong relationship between lecturer influence and online learning, showing a significant positive correlation (r = 0.693, p < .01). The findings suggest that the quality of the surrounding environment significantly influences the effectiveness of online learning, as shown by a strong positive correlation (r = 0.678, p < .01). The study found a strong positive relationship (r = 0.678, p < .01) between self-efficacy and online learning. The findings suggest that individuals who have higher levels of self-efficacy tend to experience more effective online learning. This implies that learners who believe in their capabilities and have confidence in their ability to succeed in an online learning environment are more likely to perform well.